Biological activity an in silico toxicity of phenolic compounds found in cupuaçu seed (Theobroma grandiflorum) (Research, Society and Development, 2024)
Cupuaçu (Theobroma grandiflorum) from the Malvaceae family, has seeds rich in flavonoids. The biological activities of seeds are diverse, however, there are scarce data on these metabolites. The study aimed to evaluate, through in silico methods, the biological, toxicological, and pharmacokinetic potential of metabolites present in the cupuaçu seed. The metabolites hypolaetina 3'-methylether 8-O-β-D glucuronide, theograndin II, hypolaetina 3'-methylether 8-O-β-D 3”-sulfated glucuronide, isoscutellarein 8-0-β-D glucuronide and theograndin I were analysed through Pubchem to search for structures, and PreADMET (pharmacokinetics and toxicity) and PASS online for biological activities (PA >98%). The results demonstrated low human intestinal absorption, in addition to weak to moderate distribution across the blood-brain barrier. All phenolic compounds showed weak to moderate binding to plasma proteins and low permeability in CaCo2 cells, except for isoscutelarein 8-0-β-D glucuronide and hypolaetina 3'-methylether 8-O-β-D glucuronide with moderate permeability, being non-mutagenic. Furthermore, they had the potential to inhibit CYPs, such as CYP-2C9 and CYP-3A4. Also, the structures showed toxicity in Medaka fish, but they did not present toxicity in algae and Daphnia sp. Finally, the molecules presented the following main properties: hemostatic, cardioprotective, and antioxidant action, among others. The compounds presented varied biological activity profiles, but their pharmacokinetic and toxicity were not promising, limiting the potential for developing new drugs. The use of technologies is suggested to transform them into prodrugs, carriers, and the use of molecular modeling.